Estrategias de marketing digital de la Lubricadora “Valverde” ubicado en la ciudad de Vinces durante el periodo 2023. - Salinas Santillán, Helen Eliana (2024)
This case study focuses on evaluating Valverde Lubricator, a company with more than 20 years of experience in the automotive industry. You face significant challenges with a limited digital presence and ineffective marketing strategies. Therefore, its objective is to develop and implement specific digital marketing strategies for the “Valverde” Lubricants company based in the city of Vinces for the period until 2023. Purpose of the strategies This strategy is to significantly improve the visibility of the company on the Internet. and increase your customer base. acquired from the automotive industry. The qualitative approach, supported by a bibliographic review, highlights the importance of digital marketing in relation to the reality of business. A methodological framework that addresses research questions is adopted, and the qualitative research is based on the review of existing literature. La Lubricadora Valverde, founded in 2002, has clear objectives and complies with Ecuadorian regulations. However, the lack of digital presence negatively impacts your financial and administrative management, internal processes and commercial management. Key digital marketing strategies are identified, such as Inbound Marketing, Content Marketing, and effective use of social media platforms. The results of the investigation reveal a limited digital presence and lack of effective strategies at Lubricadora Valverde. These challenges include high competition and lack of knowledge in digital marketing. Lack of action suggests lost opportunities to promote the brand and increase sales. Recommendations include establishing active profiles on key social networks, creating authentic content supported by images and videos, training staff in digital marketing, and diversifying communication channels. The implementation of these strategies is essential for the digital transformation and long-term success of Lubricadora Valverde in a digitally competitive market.